Question
upstudy study bank question image url

2. Sendo \( \operatorname{sen} x+\cos x=\frac{\sqrt{5}}{4} \), calcule: \( \begin{array}{ll}\text { a) } \operatorname{sen} x \cdot \cos x & \text { b) } \operatorname{sen}^{3} x+\cos ^{3} x\end{array} \)

Ask by Vaughan Martin. in Brazil
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a) \( \sin x \cdot \cos x = -\frac{11}{32} \) b) \( \sin^{3} x + \cos^{3} x = \frac{43\sqrt{5}}{128} \)

Solution

Dado que sen x + cos x = √5/4, siga os passos abaixo: a) Para encontrar sen x · cos x, note que:   (sen x + cos x)² = sen² x + 2 sen x cos x + cos² x                    = 1 + 2 sen x cos x   Portanto:   (sen x + cos x)² = 1 + 2 sen x cos x   ⇒ 2 sen x cos x = (sen x + cos x)² – 1. Calculando (sen x + cos x)²:   (sen x + cos x)² = (√5/4)² = 5/16 Logo:   2 sen x cos x = 5/16 – 1 = (5 – 16)/16 = -11/16   ⇒ sen x cos x = (-11/16) ÷ 2 = -11/32. b) Para calcular sen³ x + cos³ x, use a fatoração para soma de cubos:   sen³ x + cos³ x = (sen x + cos x)(sen² x – sen x cos x + cos² x). Mas sabemos que:   sen² x + cos² x = 1. Assim:   sen³ x + cos³ x = (sen x + cos x)(1 – sen x cos x). Substitua sen x + cos x = √5/4 e sen x cos x = -11/32:   sen³ x + cos³ x = (√5/4) [1 – (–11/32)] = (√5/4)[1 + 11/32]. Calculando 1 + 11/32:   1 = 32/32, então 1 + 11/32 = (32 + 11)/32 = 43/32. Logo:   sen³ x + cos³ x = (√5/4) * (43/32) = 43√5 / 128. Resumindo: a) sen x · cos x = -11/32 b) sen³ x + cos³ x = 43√5/128

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Para resolver \( \operatorname{sen} x + \cos x = \frac{\sqrt{5}}{4} \), vamos primeiro elevar ambos os lados ao quadrado: \[ (\operatorname{sen} x + \cos x)^2 = \left(\frac{\sqrt{5}}{4}\right)^2 \] Isso dá: \[ \operatorname{sen}^2 x + 2\operatorname{sen} x \cos x + \cos^2 x = \frac{5}{16} \] Sabendo que \( \operatorname{sen}^2 x + \cos^2 x = 1 \), temos: \[ 1 + 2\operatorname{sen} x \cos x = \frac{5}{16} \] Subtraindo 1 de ambos os lados: \[ 2\operatorname{sen} x \cos x = \frac{5}{16} - 1 = \frac{5}{16} - \frac{16}{16} = \frac{-11}{16} \] Portanto, isolamos \( \operatorname{sen} x \cdot \cos x \): \[ \operatorname{sen} x \cdot \cos x = \frac{-11}{32} \] Agora para o segundo item: Para calcular \( \operatorname{sen}^3 x + \cos^3 x \), podemos usar a fórmula de soma de cubos: \[ \operatorname{sen}^3 x + \cos^3 x = (\operatorname{sen} x + \cos x)(\operatorname{sen}^2 x - \operatorname{sen} x \cos x + \cos^2 x) \] Já sabemos que \( \operatorname{sen} x + \cos x = \frac{\sqrt{5}}{4} \) e que \( \operatorname{sen}^2 x + \cos^2 x = 1 \), então: \[ \operatorname{sen}^2 x - \operatorname{sen} x \cos x + \cos^2 x = 1 - \operatorname{sen} x \cos x \] Substituindo \( \operatorname{sen} x \cdot \cos x = \frac{-11}{32} \): \[ 1 - \operatorname{sen} x \cos x = 1 - \frac{-11}{32} = 1 + \frac{11}{32} = \frac{32 + 11}{32} = \frac{43}{32} \] Agora, substituímos tudo na fórmula de soma de cubos: \[ \operatorname{sen}^3 x + \cos^3 x = \left(\frac{\sqrt{5}}{4}\right)\left(\frac{43}{32}\right) = \frac{43\sqrt{5}}{128} \] Portanto, as respostas são: a) \( \operatorname{sen} x \cdot \cos x = \frac{-11}{32} \) b) \( \operatorname{sen}^3 x + \cos^3 x = \frac{43\sqrt{5}}{128} \)

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy